The Role of Neurodevelopmental Pathways in Brain Tumors - Curry, Rachel N.; Glasgow, Stacey M. (Frontiers in Cell and Developmental Biology, 2021)
Disruptions to developmental cell signaling pathways and transcriptional cascades have been implicated in tumor initiation, maintenance and progression. Resurgence of aberrant neurodevelopmental programs in the context of brain tumors highlights the numerous parallels that exist between developmental and oncologic mechanisms. A deeper understanding of how dysregulated developmental factors contribute to brain tumor oncogenesis and disease progression will help to identify potential therapeutic targets for these malignancies. In this review, we summarize the current literature concerning developmental signaling cascades and neurodevelopmentally-regulated transcriptional programs. We also examine their respective contributions towards tumor initiation, maintenance, and progression in both pediatric and adult brain tumors and highlight relevant differentiation therapies and putative candidates for prospective treatments.